Demons and Illness from Antiquity to the Early-Modern Period - Bhayro, Siam; Rider, Catherine (Magical and religious literature of Late Antiquity, 2017)
Preliminary Material -- Introduction /Siam Bhayro and Catherine Rider -- Shifting Alignments: The Dichotomy of Benevolent and Malevolent Demons in Mesopotamia /Gina Konstantopoulos -- The Natural and Supernatural Aspects of Fever in Mesopotamian Medical Texts /András Bácskay -- Illness as Divine Punishment: The Nature and Function of the Disease-Carrier Demons in the Ancient Egyptian Magical Texts /Rita Lucarelli -- Demons at Work in Ancient Mesopotamia /Lorenzo Verderame -- Demons and Illness in Second Temple Judaism: Theory and Practice /Ida Fröhlich -- Illness and Healing through Spell and Incantation in the Dead Sea Scrolls /David Hamidović -- Conceptualizing Demons in Late Antique Judaism /Gideon Bohak -- Oneiric Aggressive Magic: Sleep Disorders in Late Antique Jewish Tradition /Alessia Bellusci -- The Influence of Demons on the Human Mind according to Athenagoras and Tatian /Chiara Crosignani -- Demonic Anti-Music and Spiritual Disorder in the Life of Antony /Sophie Sawicka-Sykes -- Over-Eating Demoniacs in Late Antique Hagiography /Sophie Lunn-Rockliffe -- Miracles and Madness: Dispelling Demons in Twelfth-Century Hagiography /Anne E. Bailey -- Demons in Lapidaries? The Evidence of the Madrid ms Escorial, h.I.15 /M. Carolina Escobar Vargas -- The Melancholy of the Necromancer in Arnau de Vilanova’s Epistle against Demonic Magic /Sebastià Giralt -- Demons, Illness, and Spiritual Aids in Natural Magic and Image Magic /Lauri Ockenström -- Between Medicine and Magic: Spiritual Aetiology and Therapeutics in Medieval Islam /Liana Saif -- Demons, Saints, and the Mad in the Twelfth-Century Miracles of Thomas Becket /Claire Trenery -- The Post-Reformation Challenge to Demonic Possession /Harman Bhogal -- From A Discoverie to The Triall of Witchcraft: Doctor Cotta and Godly John /Pierre Kapitaniak -- Healing with Demons? Preternatural Philosophy and Superstitious Cures in Spanish Inquisitorial Courts /Bradley J. Mollmann -- Afterword: Pandaemonium /Peregrine Horden -- Index of Subjects -- Index of Texts.